2001
DOI: 10.1136/thorax.56.12.902
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and morphological analysis of the vascular bed in bronchial biopsy specimens from asthmatic and non-asthmatic subjects

Abstract: Background-This study was designed to establish the number and area (as a percentage) of bronchial wall vessels in subjects with and without asthma, to obtain information on the morphology of the vessels, and to see whether changes diVered in patients with mild, moderate, and severe asthma. Methods-Biopsy specimens were taken using a rigid bronchoscope from the carina of the middle lobe bronchus of 20 patients with allergic asthma and 20 non-asthmatic controls. Specimens were sectioned and stained with haemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
143
1
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(158 citation statements)
references
References 14 publications
9
143
1
5
Order By: Relevance
“…HARMANCI et al [43] demonstrated that bronchial wall thickening was more prominent with increased severity, decreased forced expiratory volume in one second (FEV1) values and the duration of asthma. The submucosa of asthmatic subjects contained more blood vessels; this also correlated with the severity of the disease [44].…”
Section: Is Remodelling Positively Correlated To Disease Severity?mentioning
confidence: 93%
“…HARMANCI et al [43] demonstrated that bronchial wall thickening was more prominent with increased severity, decreased forced expiratory volume in one second (FEV1) values and the duration of asthma. The submucosa of asthmatic subjects contained more blood vessels; this also correlated with the severity of the disease [44].…”
Section: Is Remodelling Positively Correlated To Disease Severity?mentioning
confidence: 93%
“…The increased deposition of extracellular matrix in pulmonary vessels and parenchyma in asthma presents a significant clinical implication and has an important correlation with asthma severity, including airflow limitation and bronchial hyperresponsiveness (4,16,21,31,48,49,58,59). Although there are differences between human asthma and murine models of asthma, we are aware that animals do not develop asthma and that there are several limitations in animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…The density of vessels in the medium (2-5mm inner diameter) and small (<2mm) airways is significantly elevated in mild and moderate-to-severe asthma compared to healthy controls or subjects with COPD [7] and has been linked to asthma severity [78,82]. Furthermore, the increased density of vessels was reported to be associated with asthmatic subjects with the most hyperresponsive airways [83].…”
Section: Vascular Inflammation and Remodelling Processes In Asthmamentioning
confidence: 99%